2017
DOI: 10.1371/journal.pone.0186136
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and hyperandrogenism drive steatosis and fibrosis risk in young females with PCOS

Abstract: Background and aimsNonalcoholic fatty liver disease (NAFLD) and polycystic ovary syndrome (PCOS) recognize obesity and insulin resistance (IR) as common pathogenic background. We assessed 1) whether PCOS is a risk factor for steatosis, and 2) the impact, in PCOS patients, of IR and hyperandrogenism on steatosis and fibrosis.MethodsWe considered 202 consecutive Italian PCOS nondiabetic patients and 101 age-matched controls. PCOS was diagnosed applying the Rotterdam diagnostic criteria. Steatosis was diagnosed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 33 publications
3
31
0
4
Order By: Relevance
“…Also, Vassilatou and colleagues (29) observed that LAP is a useful indicator for detecting NAFLD diagnosed by ultrasonography in Caucasian premenopausal women with PCOS. In the present study, the prevalence rate of HS was 70.3% in women with PCOS, which is consistent with previous studies (30,31). LAP is also higher in HS group than that in control group, and further LAP could independently predict the risk for HS after controlling for the potential confounding factors.…”
Section: Discussionsupporting
confidence: 92%
“…Also, Vassilatou and colleagues (29) observed that LAP is a useful indicator for detecting NAFLD diagnosed by ultrasonography in Caucasian premenopausal women with PCOS. In the present study, the prevalence rate of HS was 70.3% in women with PCOS, which is consistent with previous studies (30,31). LAP is also higher in HS group than that in control group, and further LAP could independently predict the risk for HS after controlling for the potential confounding factors.…”
Section: Discussionsupporting
confidence: 92%
“…Fibrosis in skeletal muscle can impair muscle function and affect muscle fiber regeneration after injury (Delaney et al, 2017;Mahdy, 2019). Tissue fibrosis is often initiated and maintained through TGF-beta signaling and has been suggested to be associated with insulin resistance and steatosis in PCOS (Petta et al, 2017;Stepto et al, 2019). This association is supported by a recent paper, investigating TGF-beta ligand induced fibrosis in obese women with PCOS (Stepto et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…45 Additionally, Ovarian fibrosis is also observed in polycystic ovarian syndrome (PCOS). 47,48 One radical treatment is laparoscopic ovarian drilling (LOD) for PCOS patients. 49 In the original LOD method, using an insulated unipolar needle electrode, three to eight punctures (each with a diameter of 3 mm and a depth of 2-4 mm) are performed in the ovary by laparoscopy.…”
Section: Discussionmentioning
confidence: 99%